Development of a Nomogram for Clinical Risk Prediction of Preterm Neonate Death in Ethiopia - Hailemeskel, Habtamu Shimels; Tiruneh, Sofonyas Abebaw (Frontiers in Pediatrics, 2022)
Abstract Introduction: In 2020, over 6,500 newborn deaths will occur every day, resulting in 2.4 million children dying in their first month of life. Ethiopia is one of the countries that will need to step up its efforts and expedite progress to meet the 2030 Sustainable Development Goal. Developing prediction models to forecast the mortality of preterm neonates could be valuable in low-resource settings with limited amenities, such as Ethiopia. Therefore, the study aims to develop a nomogram for clinical risk prediction of preterm neonate death in Ethiopia in 2021. Methods: A Prospective follow-up study design was employed. The data was used to analyze using R-programming version 4.0.3 software. The Least absolute shrinkage and selection operator (LASSO) regression is used for variable selection to be retained in the multivariable model. The model discrimination probability was checked using the ROC (AUROC) curve area. The model's clinical and public health impact was assessed using decision curve analysis (DCA). A nomogram graphical presentation created an individualized prediction of preterm neonate risk of mortality. Results: The area under the receiver operating curve (AUROC) discerning power for five sets of prognostic determinants (gestational age, respiratory distress syndrome, multiple neonates, low birth weight, and kangaroo mother care) is 92.7% (95% CI: 89.9% - 95.4%). This prediction model was particular (specificity = 95%) in predicting preterm death, with a true positive rate (sensitivity) of 77%. The best cut point value for predicting a high or low risk of preterm death (Youden index) was 0.3 (30%). Positive and negative predictive values at the Youden index threshold value were 85.4 percent and 93.3 percent, respectively. Conclusion: This risk prediction model provides a straightforward nomogram tool for predicting the death of preterm newborns. Following the preterm neonates critically based on the model has the highest cost-benefit ratio.